TRIPLE PSYCHO-ORGANIZATIONAL SUPPORTS FOR CHANGE MANAGEMENT PROCESS - Indriastuti, Dwi; Fachrunnisa, Olivia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
Abstract: In this ever-changing era, organizations are required to be able to answer new challenges that will emerge such as globalization, rapid flow of information and rapid technological developments, resulting in increasing demand for quality employees. This forced the organization to be able to manage existing human resources properly and effectively in order to be able to keep up with the flow of change. Therefore, every organization will try to increase the commitment of its employees, especially the commitment to change. Employees are required to have a high commitment in dealing with change and have behaviors that support change, so that they are in accordance with the changing times and demands of the community, so that the organization can still exist and not be abandoned by its users. This study aims to develop a model to find out how to encourage individual behavior support to change by increasing individual commitment to change within an organization. Change oriented leadership, employee adaptability and the internalization of organizational values which we termed as three psycho-organizational supports are indicated as important antecedents to commitment to change, which in turn will encourage individual behavior to support to change. Research Methods: Data was collected from 116 respondents as employees in Statistical Bureau Province, Indonesia. The analytical method uses SEM (Structural Equational Modeling) to test the hypotheses. Sobel Test is used to test the effect of mediating variables in the model. Finding: Behavior to support change is strongly influenced by individual commitment to change, the higher the individual's commitment to change, the more they will encourage the individual to have behaviors that support change. While individual commitment to change is influenced by several factors such as change-oriented leadership, employee adaptability and organizational values. These three factors have a positive and significant influence on individual commitment to change. Keywords: Change-oriented leadership; employee adaptability; organizational values; commitment to change; behavior to support to change.